2019
DOI: 10.1017/s1047951118002536
|View full text |Cite
|
Sign up to set email alerts
|

High acetylsalicylic acid dosing in infants after modified Blalock–Taussig shunt

Abstract: ObjectiveShunt-related adverse events are frequent in infants after modified Blalock–Taussig despite use of acetylsalicylic acid prophylaxis. A higher incidence of acetylsalicylic acid-resistance and sub-therapeutic acetylsalicylic acid levels has been reported in infants. We evaluated whether using high-dose acetylsalicylic acid can decrease shunt-related adverse events in infants after modified Blalock–Taussig.MethodsIn this single-centre retrospective cohort study, we included infants ⩽1-year-old who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Heparin-coated polytetrafluoroethylene shunts did not result in histopathologic differences compared to uncoated shunts, nor did their use eliminate the risk for shunt thrombosis ( 34 , 46 ). One single-center study of 68 patients compared “low” (<7 mg/kg/day) and “high” (≥8 mg/kg/day) empiric dosing of aspirin and found no difference in shunt thrombosis rates ( 47 ). One study reported shunt complications and interstage mortality when considering a variety of diagnoses, surgical interventions, and shunt types ( 48 ).…”
Section: Shuntsmentioning
confidence: 99%
“…Heparin-coated polytetrafluoroethylene shunts did not result in histopathologic differences compared to uncoated shunts, nor did their use eliminate the risk for shunt thrombosis ( 34 , 46 ). One single-center study of 68 patients compared “low” (<7 mg/kg/day) and “high” (≥8 mg/kg/day) empiric dosing of aspirin and found no difference in shunt thrombosis rates ( 47 ). One study reported shunt complications and interstage mortality when considering a variety of diagnoses, surgical interventions, and shunt types ( 48 ).…”
Section: Shuntsmentioning
confidence: 99%
“…31 In addition, other reports indicated that a pragmatic approach of higher dosages of aspirin (>7 mg/kg/day) may not be sufficient to reduce shunt-related adverse events in infants following modified Blalock-Taussig shunt replacement. 32 These studies suggest the need for platelet function testing and measurement of serum TXB 2 and urinary 11-dehydro-TXB 2 concentrations to determine the appropriate dosing for effective platelet inhibition.…”
Section: Antiplatelet Monitoring Based On Targeted Range Of Platelet Inhibitionmentioning
confidence: 99%
“…7 Moreover, the effectiveness of aspirin, which is commonly used in this patient population once tolerating enteral feeds, remains controversial and is without definitive guidelines for administration. [8][9][10][11][12] Despite the plethora of US Food and Drug Administrationapproved antiplatelet medications for use in adults at high risk for cardiovascular events, neonatal application of these agents is limited because of a lack of information regarding dosing, safety profile, and potential efficacy. 13,14 Thus, many are used off-label with dire consequences as the prevention of thrombosis must be balanced with the risk of bleeding, which is a major concern following palliative surgery for complex CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the early institution of unfractionated heparin as parenteral thromboprophylaxis appears to be ineffective at preventing such events, which are initiated predominantly by platelet aggregation rather than activation of the coagulation system 7 . Moreover, the effectiveness of aspirin, which is commonly used in this patient population once tolerating enteral feeds, remains controversial and is without definitive guidelines for administration 8‐12 …”
Section: Introductionmentioning
confidence: 99%